Topical Therapy of Acute Pharyngitis in Children - Yu.K. Bolbot (Zaslavsky O.Yu., 2015)
The paper discusses the methods of topical antiinflammatory therapy for acute pharyngitis in children. The analysis of the complex of mechanisms (antiinflammatory, local analgesic ones) of Tantum Verde® action and method of its application are provided.